Pengaruh Work Life Balance dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Dinas Lingkungan Hidup Kabupaten Kolaka - Almansyah Rundu Wonua; Andry Stephanie Titing; Mardayanti Mardayanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine : (1) The Effect Of Work Life Balance On The Performance Of Employees Of The Kolaka District Environmental Service Office. (2) The Effect Of Work Discipline On The Performance Of Employees Of The Kolaka District Environmental Service Office. This study used a quantitative method approach. The sample in this study amounted to43 respondents using the sampling technique, namely the census. Research instrument testing using validity test and reliability test with SPSS 24.00.The research data analysis technique uses the Structural Equating Modeling (SEM-PLS) method with Smart PLS 4.0. Based on the results of this study, it can be seen that the work life balance variable has a positive and significant effect on Employee Performance as shown by the T-Statistic value of 2.814 and P-values of 0.002, and work discipline variables have a positive and significant effect on Employee Performance as shown by the T-Statistic value of 2.266 and P-values of 0.012.